1961
DOI: 10.1021/jo01066a057
|View full text |Cite
|
Sign up to set email alerts
|

16α-Hydroxysteroids. X.1 2β-Hydroxylation of 9α-Fluorohydrocortisone by Streptomyces roseochromogenus

Abstract: 2859described18 using a Neurospora sp. (M 714). The methylene chloride extracts were concentrated to dryness, dissolved in 10% ethyl acetate in benzene and chromatographed on 1400 g. of silica gel. The chromatographic column was eluted successively with 10%, 12%, 15%, 25%, 35%, 40%, and 50% ethyl acetate in benzene. The 50% eluates were concentrated to dryness and the residue was crystallized from acetone,cyclohexane, then from methanol, and finally from acetonecyclohexane again to yield 394 mg. of 7a-hy droxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1961
1961
2000
2000

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Selective hydroxylation of the double bond at position 16 with osmium tetroxide in pyridinebenzene gives compound 127. The 9,11-double bond of this compound is converted to a 9α-fluoro-11β-hydroxyl group (128) by the method described for 9α-fluorocortisol (123) The 16α-hydroxyl group can also be introduced directly into 9α-fluoroprednisolone (124) by using a microbiological method originally developed by Squibb [253,254]. Triamcinolone 16α,17α-acetonide (130) is prepared by stirring a suspension of triamcinolone (129) in acetone in the presence of catalytic amounts of perchloric acid at approximately 20…”
Section: -Hydroxycorticosteroidsmentioning
confidence: 99%
“…Selective hydroxylation of the double bond at position 16 with osmium tetroxide in pyridinebenzene gives compound 127. The 9,11-double bond of this compound is converted to a 9α-fluoro-11β-hydroxyl group (128) by the method described for 9α-fluorocortisol (123) The 16α-hydroxyl group can also be introduced directly into 9α-fluoroprednisolone (124) by using a microbiological method originally developed by Squibb [253,254]. Triamcinolone 16α,17α-acetonide (130) is prepared by stirring a suspension of triamcinolone (129) in acetone in the presence of catalytic amounts of perchloric acid at approximately 20…”
Section: -Hydroxycorticosteroidsmentioning
confidence: 99%
“…the aldehyde IV does not appear to be a biological intermediate in the formation of 21-acetylamino-9 -fluoro -11,3,17 -dihydroxy -4 -pregnene-3,20-dione from I by S. roseochromogenus (Smith et al, 1962). The aldehyde IV is not hydroxylated by S. roseochromogenus; neither 16 a-nor 2/3hydroxylated derivatives could be detected.3 Experimental 9a-Fluoro-l 1ß,17 a,203,21 -tetrahydroxy-4-pregnen-3-one (II).-The steroid-rich broth extract concentrate obtained from S. roseochromogenus fermentations of 9a-fluorohydrocortisone already described (Smith et al, 1961) was used for the isolation of 20/3-dihydro-9a-fluorohydrocortisone. An initial separation of some non-steroidal materials was accomplished by adsorption of the extract concentrate onto silica gel from ethyl acetate.…”
mentioning
confidence: 97%
“…In our studies of the 16 -hydroxy latió n of 9afluorohydrocortisone (I) by Streptomyces roseochromogenus a variety of reducing (Smith et al, 1960b;Smith et al, 1961) and non-reducing (Smith et al, 1962) steroids have been isolated and identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that Streptomyces roseochromogenes, in addition to hydroxylating 9a-fluorohydrocortisone in the 16a-position (Thoma et al, 1957), is able to affect hydroxylation in the 2,3-position to yield both 2(3-hydroxy-9a-fluorohydrocortisone and the 2#3, 16adihydroxy-9a-fluorohydrocortisone. The isolation and structure proof of the 2,B-hydroxylated products are presented elsewhere (Smith et al, 1961). The degree of 2,B-hydroxylation was found to be highly strain dependent.…”
mentioning
confidence: 99%